The influence of external barriers in business model innovation : Bibliometric citation analysis approach - Maharjan, Bimi (My University, 2021)
A business model is an emerging idea in every business firm to regulate its business activities systematically. Innovation relates to the business model as development and controlling the strategic plans for sustainability of the firm. As development and refinement, the firms face challenges and barriers in business model formation and innovation. The structure of the study starts with the introduction of the comprehensive research and research gap. The theoretical background explains the business model, business model innovation, and external barriers. The academic study of the knowledge of the study shows the gap in the research of the influence of the external obstacles in business model innovation. The purpose of the research is to study the influences of external barriers in business model innovation—the bibliometric citation analysis used to analyze the database of articles. The analysis gives us the pattern of articles related to the business model and external barriers. The citation graph from the analysis provides key research streams that help fulfill the study's main research area. The database of articles is 200 articles in total as the papers are selected based on high citations, and the citation graph has a limitation of 30 documents to form the mapping of the articles. The method of the study uses HistCite software for the analysis of the reports. The papers' database contains 200 articles from 1995-2018 created by the Web of Science Core Collection. The selection of articles from 1995-2018 is to build the database of highly cited papers. External barriers are mainly concerned with technological advancement, strategic decisions, competitive pressure, and government regulations from the data analysis. The research streams in which most of the articles point out the technical development and strategic decisions mainly influence the business model innovation. Likewise, most of the research streams indicate that the business model regulates the firm's activities and competition, and new regulations of the government policies initiate as the external barriers in the business model innovation.